When vulnerability got mainstream: Reading the pandemic through disability and illness - Pieri, Mara (2022)
Since its outbreak, the COVID-19 pandemic has generated discourses and practices that directly refer to the semantic universe usually connected to disability and illness. Words such as ‘pre-existing conditions’, ‘risk groups’, ‘accessibility’, and ‘vulnerability’ have become everyday elements of official and informal communications across the globe. In this article, I explore the contradictions that arise from such uses through the lens of crip studies. In the first part, I observe how the idea of vulnerability became mainstream, moving from being usually attached to disability and illness to being depicted as a universal condition. Such a shift serves the double purpose of reinstating the predominance of able-bodiedness as the preferable normalcy and invisibilising the particular conditions of disabled and chronically ill people in the pandemic. In the second part, I discuss the perverse use of the expressions ‘risk group’ and ‘underlying conditions’ as biopolitical tools to reinforce already existing forms of oppression. The third part comprises a reflection on accessibility and the sudden advent of working-from-home. Finally, I reflect on confinement and interdependence as key concepts to draft a politics of transformation that moves from disability and chronic illness to include all experiences of intersectional oppression. As other markers of oppression, illness and disability can determine the possibilities of survival through the crisis, not only because they are linked to bodily fragility but also because of the systemic violence they are immersed in. The knowledge produced from a place of vulnerability can hence show interesting elements to better understand the challenges of this pandemic through an intersectional perspective.